Infection Prevention and Control Practice Regarding Tuberculosis Among Primary Healthcare Workers in Sokoto Metropolis, Sokoto State, Nigeria - Malami Muhammad Bello; Umar Muhammad Ango; Habibullah Adamu; Abdul’aziz Mohammad Danmadami; Hudu Garba Illo; Abdullahi Shehu; Zaharadeen Muhammad Dan-Inna (Journal of Community Medicine and Public Health Research, 2026)
Tuberculosis remains a major public health concern, necessitating effective infection prevention and control practices among healthcare workers, especially in high-burden areas. The aim of this study was to assess the knowledge and practice of Tuberculosis Infection Prevention and Control (TBIPC) among primary healthcare workers in primary healthcare facilities across selected Local Government Areas in Sokoto, Nigeria. This was a cross-sectional study conducted among 155 primary healthcare workers selected using a multistage sampling technique. Data were collected using a set of pretested, interviewer-administered questionnaires via Open Data Kit (ODK). The questionnaire assessed respondents' knowledge and practice of TBIPC. Data were analysed using IBM SPSS version 25. Descriptive statistics, such as frequencies and proportions for categorical variables, as well as means and standard deviations for continuous variables, were obtained. Pearson’s chi-square and Fisher’s exact tests were used to determine the factors associated with TBIPC practice among the study participants. The mean age of respondents was 31.29 ± 8.90 years, and the dominant age group was 20–29-year-olds, constituting 43.9% of respondents. The majority (96.1%) had poor knowledge, and only 13.5% had good practice regarding TBIPC. More than one-third (31.4%) of trained respondents demonstrated good practice, compared with 4.2% of untrained respondents (p < 0.001). Similarly, those with good knowledge of TBIPC were more likely to have good TBIPC practice (15.7% vs 5.9%). TBIPC knowledge and practice among PHC workers were poor, and both training and knowledge were significantly associated with better practice.